Government Support and Local Residents’ Behavior in E-waste Management: Evidence from Thailand - Peeranart Kiddee; Somsiri Decharat; Suttiporn Bunmak (Applied Environmental Research)
Electronic waste (e-waste) management is a critical global pollution concern. This study investigates government support; local residents' perceptions, knowledge, attitudes, and behaviors related to e-waste management; and collaborative governance in southern Thailand. Employing both quantitative and qualitative methods, this research involves expert government officers who are well versed in e-waste management and local residents. The study utilized in-depth interviews, questionnaires, and workshops. The results revealed that the government is responsible for four e-waste management approaches, encompassing various e-waste collection, transportation, and disposal methods. Local residents exhibited low perceptions of e-waste news but possessed substantial knowledge and positive attitudes toward e-waste management. Surprisingly, general characteristics do not significantly influence e-waste management behavior. A statistically significant connection was found between perceptions (B = 0.065, t = 6.657, p value = 0.000) and attitudes (B = 0.079, t = 4.350, p value = 0.000) toward e-waste management, which had a positive relationship with e-waste management behavior in southern Thailand (p value < 0.01). Repairing appliances is the most common action taken (44.5%). Despite longer lifespans for electronic appliances than they did a decade ago, revisions to the draft waste electrical and electronic equipment Act are underway, aiming to incorporate stakeholder involvement and the extended producer responsibility principle. This study provides valuable insights into government and local community concerns regarding e-waste management and evaluates the efficacy of recent management procedures. These findings can inform the development of action plans that consider crucial aspects of e-waste management.